INFECTIOUS MONONUCLEOSIS AS A MODEL OF CHRONIC VIRAL INFECTION BASED ON A PERSONAL CLINICAL OBSERVATION (Multidisciplinary Journal of Science and Technology, 2025)
This article considers infectious mononucleosis not only as an acute disease but also as a unique model of chronic viral infection that allows understanding the mechanisms of long-term viral persistence in the human body. The work details the properties of the Epstein–Barr virus, the features of its interaction with the immune system, factors contributing to the chronicity of the process, as well as the clinical manifestations and complications of the disease. Modern approaches to diagnosis and treatment are presented, and the role of EBV infection in the development of autoimmune and oncological diseases is discussed. A clinical case from the author’s own observation of a pediatric patient is also described.